Effects of reactive oxygen species on skin photoaging - Anna M. Augustyniak; Helena Rotsztejn; Ewelina Bartnicka; Elżbieta Budzisz (Termedia Publishing House, 2016)
The large surface area of the skin, high metabolism and location at the border of two environments (external and internal) cause continuous production of free radicals within the skin. There are two mechanisms of skin photoaging. The first one involves UVA-induced production of reactive oxygen species. The second mechanism is based on a direct interaction of UVB with DNA and induction of damage in the DNA structure. One way by which UVA leads to skin aging is activation of the AP-1 transcription factor due to singlet oxygen, which is released by UV radiation. Antioxidants slow down oxidation leading to the formation of free radicals, or inactivate already formed free radicals, and thereby accelerate interruption of chain reactions. Moreover, photoprotection has a key role in combating photoaging and eliminating its effects.